King Arthur in the Medieval Low Countries - Claassens, Geert (Mediaevalia Lovaniensia - Series 1/Studia, 2000)
The Arthurian myth is one of the most fundamental and abiding ones of Western culture. The legend of King Arthur and his knights was no less popular in the medieval Low Countries than it was anywhere else in medieval Europe. It gave rise to a varied corpus of Middle Dutch Arthurian verse romances, most of which are contained in a single manuscript, the so-called Lancelot Compilation of MS The Hague, KB, 129 A10. This manuscript of the early fourteenth century contains a cycle of verse narratives that rivals in its scope and thematic concerns the better known Old French Vulgate Cycle of Arthurian tales and Sir Thomas Malory's Morte Darthur. This volume contains new critical work on these and other Middle Dutch Arthurian romances, twelve studies by eleven established scholars in the field of Arthurian literature. In addition to this new scholarship, the volume is provided with an extensive introduction to the Arthurian literature of the medieval Low Countries, as well as summaries of all the extant Middle Dutch Arthurian texts. As such it should prove of interest to Arthurian specialists and enthusiasts alike, many of whom will discover a new body of Arthurian tales, at once both familiar and new, in a heretofore relatively neglected area of Arthurian studies.